Japan Decides 2017 The Japanese General Election (Springer International Publishing, 2018)
This third volume in the Japan Decides series remains the premier venue for scholarly research on Japanese elections. Putting a spotlight on the 2017 general election, the contributors discuss the election results, party politics, coalition politics with Komeito, the cabinet, constitutional revision, new opposition parties, and Abenomics. Additionally, the volume looks at campaigning, public opinion, media, gender issues and representation, North Korea and security issues, inequality, immigration and cabinet scandals. With a topical focus and timely coverage of the latest dramatic changes in Japanese politics, the volume will appeal to researchers and policy experts alike, and will also make a welcome addition to courses on Japanese politics, comparative politics and electoral politics. .